2008
DOI: 10.4162/nrp.2008.2.1.26
|View full text |Cite
|
Sign up to set email alerts
|

Household food insecurity and coping strategies in a poor rural community in Malaysia

Abstract: This cross-sectional study assessed household food insecurity among low-income rural communities and examined its association with demographic and socioeconomic factors as well as coping strategies to minimize food insecurity. Demographic, socioeconomic, expenditure and coping strategy data were collected from 200 women of poor households in a rural community in Malaysia. Households were categorized as either food secure (n=84) or food insecure (n=116) using the Radimer/Cornell Hunger and Food Insecurity instr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
105
4
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(125 citation statements)
references
References 42 publications
12
105
4
4
Order By: Relevance
“…In a study among low income community in Sabak Bernam, percentage of households experiencing food insecurity is above 50% (Shariff & Khor 2008). The percentage of low income households in the city that have food insecurity was higher (66.6%) compared with those in rural areas of 58% (Sharif & Ang 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In a study among low income community in Sabak Bernam, percentage of households experiencing food insecurity is above 50% (Shariff & Khor 2008). The percentage of low income households in the city that have food insecurity was higher (66.6%) compared with those in rural areas of 58% (Sharif & Ang 2001).…”
Section: Introductionmentioning
confidence: 99%
“…For their part, the work of Chagomoka et al (2016), carried out in Ghana, pointed out that households used coping strategies more frequently, such as skipping meals the whole day, borrowing food or money to buy food, consuming seed stock and purchasing food on credit. Shariff and Khor (2008) found, in a rural community in…”
Section: Discussionmentioning
confidence: 99%
“…The coping strategy questionnaire was created using different bibliographic references (Maxwell and Caldwell, 2008;Shariff and Khor, 2008;Ngidi and Hendriks, 2014;Gupta et al 2015).…”
Section: Research Objective and The Empirical Context Of The Thesismentioning
confidence: 99%
See 1 more Smart Citation
“…The first strategy stated by Kabeer (1990) could be categorized as negative and second as positive strategy (except when children are drawn to work) [24]. Castaneda et al (2000) and Shariff and Khor (2008) also found that employed members were drawn to more odd jobs during food insecurity in order to increase resources [25,26]. These strategies could be considered positive as they increase the household resources to buy food and thus ameliorate food insecurity.…”
Section: Discussionmentioning
confidence: 99%